A critical review: the impact of electrical poling on the longitudinal piezoelectric strain coefficient. Issue 24 (8th November 2022) - Dani, Sanskruti Smaranika; Tripathy, Alekhika; Alluri, Nagamalleswara Rao; Balasubramaniam, Saravanakumar; Ramadoss, Ananthakumar
Abstract : This review elaborates on the importance of poling and its theories, parameters, techniques and d 33 values of lead-based and lead-free materials and its composites. The energy-harvesting performance, current challenges, and prospects are also discussed. Abstract : Piezoelectric materials play an essential role in the advancement of micro- and nanoelectronics equipment. The piezoelectric properties of the materials rely upon the degree of polarization that results from the poling mechanism. The present study put forward the improvement of piezoelectric performance by optimizing the poling parameters in piezoelectric materials. Microstructural optimization of flexible piezoelectric-based material is one possible technique to improve the electrical responses of the piezoelectric nanogenerator. In particular, the correlation between the poling conditions and the longitudinal figure of merit ( d 33 ) of various materials (lead-based, lead-free and polymers and their composites) provides an effective analysis to supplement the available literature. This report examines the latest research progress in different poling techniques and their consequences for achieving the required beta-phase of a polyvinylidene fluoride (PVDF) film with a higher electrical output. Finally, novel poling techniques, the current challenges, and prospects are highlighted and critically discussed, currently which is relatively untouched research field for the scientific community. We believe that this review affords systematic guidelines for poling techniques that can significantly contribute to subsequent piezoelectric nanogenerator (PENG) research.